2006
DOI: 10.1542/peds.2005-0294
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Lymphocyte Populations, Plasma HIV RNA Levels, and Disease Progression in a Cohort of Children Born to Women Infected With HIV

Abstract: Plasma RNA levels differed among antiretroviral therapy-treated, HIV-infected children according to gender, in a manner similar to that noted in previous pediatric and adult studies. Lymphocyte subsets varied according to gender in a cohort of HIV-exposed but uninfected children. Most importantly, overall mortality rates for this cohort differed according to gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
2
26
3
Order By: Relevance
“…It is also conceivable that some children that were lost to follow-up had actually died, which might have affected both the validity and precision of our estimate as pointed out by an earlier systemic analysis done in 2009 [58]. However, a recent systemic review in 2017 suggests that more of sub-Saharan HIV-infected patients that are lost to follow-up are surviving better [59].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…It is also conceivable that some children that were lost to follow-up had actually died, which might have affected both the validity and precision of our estimate as pointed out by an earlier systemic analysis done in 2009 [58]. However, a recent systemic review in 2017 suggests that more of sub-Saharan HIV-infected patients that are lost to follow-up are surviving better [59].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Also, the antiretroviral (ARV) prophylaxis of vertical transmission can act on the placental environment, causing changes in cytokine expression (9). The newborns present abnormalities in mitochondrial function (2), in hematological features (5,10,17), and in the maturation of T and B lymphocytes (3,4,8,11,12,20,24,25).…”
mentioning
confidence: 99%
“…Prior studies on ARV treated HIV infected individuals clearly established sex differences in HIV RNA levels and CD4 cell parameters among adults but have also presented conflicting results (15,16). There is one study of 158 children receiving ART that found HIV RNA levels to be 0.38 log lower in girls than in boys but found no difference in CD4 cell count or percentage (15).…”
Section: Discussionmentioning
confidence: 99%
“…There is one study of 158 children receiving ART that found HIV RNA levels to be 0.38 log lower in girls than in boys but found no difference in CD4 cell count or percentage (15). But there are few studies that analyzed differences on HIV RNA level and CD4 cell count in a large number of participants and none over such a long period of time.…”
Section: Discussionmentioning
confidence: 99%